A early rehabilitation trial for ischemic stroke - Witold Pawłowski; Dorota Lasota; Mariusz Goniewicz; Robert Czerski; Krzysztof Goniewicz (Kazimierz Wielki University, 2019)
An apoplectic stroke is an urgent state requiring conservative treatment and sometimes even operational. A patient should be rehabilitated from the very first days in hospital. The main aim of early rehabilitating is obtaining maximally possible movements efficiency of a patient, improvement of his or her communicating abilities and abilities of independent living. Early rehabilitation should also include prevention from complications resulting from patient's immobility. A rehabilitation program should be prepared individually for every patient. A patient after stroke should have psychological care provided which aim is to prevent from depression and abandonment that have influence on rehabilitation success. Apart from physicians and nurses who directly take care of a patient, also a rehabilitating multi-specialization team should take part in treatment. Such team should be composed of a physiotherapist, a logopedist, a clinical psychologist and an occupational therapist